El amanecer de la nación. Un aporte sobre el libro nudos y voces en la república de Boris Espezua - Diaz Montenegro, Walter (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2022)
The present work carries out a descriptive examination of the theme of the national question that Espezúa's book addresses. Emphasis has been placed on a historical-cultural contextualization that, necessarily, requires the question of identity in the face of a national perspective that we now know extends to the Inca, the Colony, the Republic and Contemporary Peru. Likewise, the works of Garcilaso de la Vega and Ga-maliel Churata have been studied in depth due to their implication in the field of the Andean Cosmovision. Very different has been the focus on Basadre and whose contribution, we believe, may have been the origin of the author's book. Finally, the last section of the book has been deepened, because it is there where the theme of the current national crisis has been reworked in the form of an affirmation, but at the same time shows the enormous impact that the crisis has caused. current in the artistic sensibility of the author.